Correction to: "Portraits from a Conjoined War: The German 100th Light Infantry Division and First Contact with the Jews of Zinkiv, Ukraine—July 1941" (Holocaust and genocide studies, 2023)
This is a correction to: Robert Bernheim, "Portraits from a Conjoined War: The German 100th Light Infantry Division and First Contact with the Jews of Zink